Cryptococcus escapes host immunity: What do we know? - Yang, Chen; Huang, Yemei; Zhou, Yangyu; Zang, Xuelei; Deng, Hengyu; Liu, Yitong; Shen, Dingxia; Xue, Xinying (Frontiers in Cellular and Infection Microbiology, 2022)
Cryptococcus is an invasive fungus that seriously endangers human life and health, with a complex and well-established immune-escaping mechanism that interferes with the function of the host immune system. Cryptococcus can attenuate the host’s correct recognition of the fungal antigen and escape the immune response mediated by host phagocytes, innate lymphoid cells, T lymphocytes, B lymphocytes with antibodies, and peripheral cytokines. In addition, the capsule, melanin, dormancy, Titan cells, biofilm, and other related structures of Cryptococcus are also involved in the process of escaping the host’s immunity, as well as enhancing the ability of Cryptococcus to infect the host.